A Unique Power to Punish: An Examination of the Operation, Scrutiny, and Attendant Risks of Licensee Barring Provisions in Victoria, Australia - Farmer, Clare (Criminal justice policy review, 2021)
Across Australia, patron banning measures address alcohol-related behavioral issues in entertainment districts. This article compares the legislative framing of Victoria’s licensee barring order policy with the experiences of recipients. The rationale and operational expectations for licensee barring are examined in relation to key themes which emerged during parliamentary debates of the legislation, and contrasted with the reported experiences of recipients. The findings point to a disconnect between the expected and actual operation of licensee barring, an absence of oversight, and a tangible risk of misuse. Barring orders extend to ordinary citizens a unique police-enforceable power to punish, yet licensees currently act without scrutiny or accountability. A review of barring policy is recommended to ensure a robust process for effective monitoring, meaningful consequences for the misuse of barring powers, and deeper consideration of the attendant risks to due process and procedural justice of the civilianisation of punishment.